Mental health nurses' beliefs about smoking by mental health facility inpatients. (16th August 2012) - Connolly, Michael; Floyd, Sue; Forrest, Rachel; Marshall, Bob
Abstract This study examined beliefs of mental health nurses about smoking by clients, nurses, and visitors in inpatient facilities and identified the influence of years of experience, smoke‐free status, and workplace on these beliefs. Data were collected by a survey, distributed via a nursing newsletter with approximately 600 members. Descriptive statistics and cross‐tabulations explored the data. A total of 104 responses were received. Smoke‐free status made significant differences to nurses' beliefs relating to prohibition of smoking for clients, staff, and visitors; concern about the effects of passive smoking; the role of smoking in the development of therapeutic relationships; smoking as a source of patient pleasure; and the role of smoking in symptom management. That half of the nurses who responded believe that smoking is helpful in the creation of therapeutic relationships is of concern. The nurse plays an important role model in promoting smoke‐free lifestyles amongst clients, and the effects of positive role modelling could be lost if nurses continue to smoke with clients. The negative impacts of smoking on the physical health of mental health inpatients is considerable and well documented, and the creation of smoke‐free inpatient mental health services can help to address these.